Distillers Grain Industry Price Discovery & Risk Management - Stroade, Jeri; Martin, Anikka; Conrad, Ann; Schroeder, Ted C. (North American Institute for Beef Economic Research; Kansas State University Agricultural Experiment Station and Cooperative Extension Service, 2010)
DG prices have become an important part of ethanol plant profitability as margins in the DG industry have narrowed over the past few years. In addition, as DG production has increased, its importance as ingredient in livestock feed has escalated. At the same time as DG has increased in importance for both ethanol plants and livestock producers, its price has seen substantial volatility.
Keywords: Distillers grain; Ethanol; Transportation; Pricing; Marketing